Ordered multiferroic CoFe2O4–Pb(Zr0.52Ti0.48)O3 coaxial nanotube arrays with enhanced magnetoelectric coupling. Issue 46 (2nd June 2017) - Tang, Dan; Zeng, Zhiqiang; Zhou, Qingwei; Su, Shaoqiang; Hu, Die; Li, Peilian; Lin, Xiaozi; Gao, Xingsen; Lu, Xubing; Wang, Xin; Jin, Mingliang; Zhou, Guofu; et al.
Abstract : In this paper, vertically free-standing multiferroic CoFe2 O4 –Pb(Zr0.52 Ti0.48 )O3 (CFO–PZT) coaxial nanotube arrays with both good ordering and high density were prepared by a template-assisted sol–gel method. Abstract : In this paper, vertically free-standing multiferroic CoFe2 O4 –Pb(Zr0.52 Ti0.48 )O3 (CFO–PZT) coaxial nanotube arrays with both good ordering and high density were prepared by a template-assisted sol–gel method. X-ray diffraction (XRD) and Raman spectra confirmed that the as-prepared CFO–PZT nanotubes (NTs) included both spinel CFO and perovskite PZT phases. The multiferroic properties were demonstrated by magnetic hysteresis and piezo-response force microscopy (PFM). We also observed an effective dielectric constant of about 0.8% between increasing and decreasing magnetic field, indicating that the ordered CFO–PZT coaxial nanotube arrays may enable potential high-density magnetoelectric (ME) devices.